Fatigue damage assessment of container ships concerning wave-induced torsion - Li, Zhiyuan; Ringsberg, Jonas; Mao, Wengang (29th International Conference on Ocean, Offshore and Arctic Engineering: Volume 2, 2010)
The traditional method to assess fatigue damage of ship structures assumes moderate wave amplitudes and linear responses. This method can be questioned when applied on container ships that are characterized by large deck openings, because the low torsion rigidity of this type of ship makes it sensitive to oblique waves. In this paper, the 3D hydrodynamic code WASIM is used to simulate a 4400 TEU container ship operating in the North Atlantic Ocean. Nonlinear wave loads are utilized for direct calculation of the stress histories under severe sea states. The warping stress from wave-induced torsion is separated from the stress components from vertical and horizontal bending. The contribution to fatigue damage accumulation from warping stresses is evaluated. For comparison, the results from the numerical simulations and fatigue calculations are verified with full-scale measurements made on a similar type of container vessel.